Forming cadets’ axiological attitude in SEM of Ukraine to professional activity - Dement, M. (Problems of Engineer-Pedagogical Education, 2018)
In the work forming cadet’s axiological attitude toward their professional activity in SEM of Ukraine is grounded. The work used a set of methods of theoretical research: a comparative analysis of scientific, educational, methodological and military literature to determine the state of the development of the research problem; analysis of normative documentation on the organization of the educational process of the higher educational institutions of the State Emergency Service of Ukraine with the purpose of determining the essence of stimulating the cadet's axiological attitude to professional activity; classification and systematization of different views on the problem of justifying modern trends and ways to encourage cadets to axiological attitude toward the professional activities. The main results of the work are: to determine the concept of cadets’ "stimulation" to professional activity and determination of basic means of stimulation, to analyse the principles of understanding the term cadet’s "axiological attitude" to the profession, to elucidate the main directions and ways of stimulating axiological attitude to cadets’ professional activity. The result of the research is the system of means for stimulating the axiological attitude to professional activity offered by the author such as organizational and activity-oriented and innovative role play, disputes, training methods aimed at stimulating an axiological attitude to professional activity.